The understanding of the social determinants factors of public acceptance towards the end of life vehicles. Issue 1 (31st December 2022) - Sitinjak, Charli; Ismail, Rozmi; Bantu, Edward; Fajar, Rizqon; Samuel, Karuhanga
Abstract: Indonesia is one of the highest producers of the automotive industry in Southeast Asia. However, rapid progress in this sector directly poses a threat to the increase in End-of-Life Vehicles in Indonesia. Several policies and instruments have been implemented to reduce the high number of ELVs, such as raising vehicle taxes and requiring periodic emissions testing systems to determine vehicle eligibility. These initiatives, however, do not reduce the use of ELV vehicles in Indonesia. Indonesia did not win the ELV because of high rejection from the users. To date, no research has been done to determine public acceptance of ELV policies. This study aims to examine the public acceptance of ELV management, particularly to gauge information about people's knowledge, attitude, social influence, and institutional trust as mediation variables. A cross-sectional survey was conducted involving 243 respondents from JABODETABEK (Jakarta, Bandung, Depok, Tangerang, Bogor, and Bekasi). After passing satisfactory reliability and validity tests, the hypothesized research model was estimated using structural equation modelling. The study found that knowledge, attitude, social influence, and institutional trust all had a significant influence on public acceptance. The result also indicated that institutional trust variables serve as effective mediators. The proposed model is a good model (overall R2 = 0.703, F = 58.2, p = 0.00). The implication of this study suggested that policymakers should consider that implementing ELV-related policies is not only a solution to the automotive cycle and environmental health but also must address individual differences by taking into the factors forming one's acceptance.